Assessing socio-economic development in Bodoland Territorial Area District of Assam in India. Issue 12 (15th October 2020) - Basumatary, Nicodim; Panda, Bhagirathi
Abstract : Purpose: The study attempts to assess the socio-economic development in Bodoland Territorial Area District (BTAD) of Assam in North Eastern Region of India. This region is one of the most underdeveloped areas in India. The study also examines whether demographic and social characteristics in the form of social groups, number of family members, number of employed members in the family, education of the head of household, sources of income and location determine the variation in the level of socio-economic development. The authors surveyed 400 households during February to May 2018 in both rural and urban areas of BTAD to achieve the objective of the study. Design/methodology/approach: The authors use the concept of Amartya Sen's capability approach (CA) for assessment of development and constructed an index of Multidimensional Development. Findings: There is variation in the distribution of developmental parameters across the study area. It is found that urban locations have better achievement in the multidimensional index score, while the spread of development is not even in the rural locations. An interesting revelation of this study is that while urban areas depict better performance in income, asset, education and empowerment, they have a relatively lower score in health dimension as compared to rural areas. The study shows that level of development depends on demographic as well as social characteristics of the households. Research limitations/implications: This study does not analyse temporal dynamics of development that is necessary to examine how development evolves because of data constraints. Originality/value: The study provides an understanding of the socio-economic development in BTAD area in a multidimensional framework. This study is the first of its kind to assess the nature and extent of development realised in BTAD through the capability framework. The study supports more recent findings.